New insight into the microbiome, resistome, and mobilome on the dental waste water in the context of heavy metal environment - Jiao, Xiaoyang; Guo, Wenyan; Li, Xin; Yao, Fen; Zeng, Mi; Yuan, Yumeng; Guo, Xiaoling; Wang, Meimei; Xie, Qing Dong; Cai, Leshan; Yu, Feiyuan; Yu, Pen; et al. (Frontiers in Microbiology, 2023)
Hospital sewage have been associated with incorporation of antibiotic resistance genes (ARGs) and mobile genetic elements (MGEs) into microbes, which is considered as a key indicator for the spread of antimicrobial resistance (AMR). The compositions of dental waste water (DWW) contain heavy metals, the evolution of AMR and its effects on the water environment in the context of high heavy metal levels have not been seriously investigated. Thus, our major aims were to elucidate the evolution of AMR in the context of high heavy metal levels in DWW. Methods: DWW samples were collected from a major dental department. The presence of microbial communities, ARGs, and MGEs in untreated and treated (by filter membrane and ozone) samples were analyzed using metagenomics and bioinformatic methods. Results: DWW-associated resistomes included 1208 types of ARGs, belonging to 29 antibiotic types/subtypes. The most abundant types / subtypes were ARGs of multidrug resistance and of antibiotics that were frequently used in the clinical practice. Pseudomonas_putida, Pseudomonas_aeruginosa, Chryseobacterium_ indologenes, Sphingomonas_ laterariae were the main bacteria which hosted these ARGs. Mobilomes in DWW consisted of 93 MGE subtypes which belonged to 8 MGE types. Transposases were the most frequently detected MGEs which formed networks of communications. For example, ISCrsp1 and tnpA.5/4/11 were the main transposases located in the central hubs of a network. These significant associations between ARGs and MGEs revealed the strong potential of ARGs transmission towards development of antimicrobial-resistant (AMR) bacteria. On the other hand, treatment of DWW using membranes and ozone was only effective in removing minor species of bacteria and types of ARGs and MGEs. Conclusion: DWW contained abundant ARGs, MGEs, and heavy metals which contributed to the occurrence and spread of AMR bacteria. Consequently, DWW would seriously increase environmental health concerns which may be different but have been well-documented from hospital waste waters.